If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(A + -6) = 0 Reorder the terms: 3(-6 + A) = 0 (-6 * 3 + A * 3) = 0 (-18 + 3A) = 0 Solving -18 + 3A = 0 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 3A = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 3A = 0 + 18 3A = 0 + 18 Combine like terms: 0 + 18 = 18 3A = 18 Divide each side by '3'. A = 6 Simplifying A = 6
| 14-3(6x-7)=2x+10-35 | | 3x=4x-(4x*0.285) | | 20+3x=36-x | | 6-6(x+2)=10+2x | | 60+3x=12-x | | 12x-7=-17 | | 20+3x=12-x | | (3xy^2)/(21x^4yz^-4) | | 3(5+6)-4(4)=2(4)-16+5(a+1) | | x/1-1/x=8/3 | | 23-3*6/9 | | 7x-2=10x-8 | | -12=-144 | | (3a-2)-(3-5a)=1 | | 7/5p-10=30 | | 8x=296 | | -6+x=-8(1-7x)+2 | | (-5x^3+2x^2-x+5)-(-5x^3+3x^2+5x+3)= | | -3.3+-9.1= | | (x+6)8=-24 | | (-8x^5y)(x^9y^2)= | | 5x-160=9x | | 36=2u+16 | | -2(1+2x)=2(4-x)+3x | | -3ab(ab-2a^2b+5a)= | | 12-8+7= | | 4(x+7)=-(x+12)+2(x+1) | | 2(7-c)-4=0 | | x/5-10=25 | | -8x+2=12 | | 4/9x/2t/3 | | 2*5=8-x |